Burden Of Care and Depression in Caregivers of Patients with Schizophrenia - Mubeen Taj; Maithreyi Poguri; Glady Mariyana; Sujitha Jebarose; christina Mary Paul (Medsci Publications, 2022)
Background: Schizophrenia, a chronic psychiatric disorder affecting all major domains of a patient's life, leads to significant disability. Since the deinstitutionalization policy, the onus of care is on families especially the primary caregiver who experiences physical and emotional burden. Depression among caregivers has been estimated to be higher than the general population. This cross-sectional study aimed to assess burden of care and depression in primary caregivers and associated caregiver variables. Methods: 75 consenting primary caregivers of patients with ICD-10 diagnosis of schizophrenia were assessed for burden of care and depression using the Burden Assessment Schedule and the Patient Health Questionnaire - 9 after collecting socio-demographic and caregiving details. Results: All the caregivers, 49 females and 26 males, had moderate to high levels of burden with a majority having moderate to severe levels of depression. Spouses (p=0.0038), older caregivers (p=0.01) and those with lower educational levels (p=0.01) experienced more burden. There was a significant positive correlation between burden of care and depression (p=0.000). Conclusion: In one of India's largest metropolitan cities, though psychiatric services are easily available, caregivers continue to feel burdened and depressed. This can impact not just the caregiver but also care being provided to the patient and illness outcome.